Insuring Well‐Being? Buyer's remorse and peace of mind effects from insurance - Tafere, Kibrom; Barrett, Christopher B.; Lentz, Erin C. (Wiley, 2019)
We estimate the causal effects of index insurance coverage on subjective well‐being among livestock herders in southern Ethiopia. By exploiting the randomized distribution of discount coupons and information treatments to instrument for the purchase of index‐based livestock insurance, and three rounds of panel data, we separately identify ex ante welfare gains from insurance that reduces risk exposure and ex post buyer's remorse effects that may arise after the resolution of uncertainty. We find that current insurance coverage generates subjective well‐being gains that are significantly higher than the buyer's remorse effect of an insurance policy that lapsed without paying out. Given the positive correlation in insurance purchase propensity over time, failure to control for potential buyer's remorse effects can bias downward estimates of welfare gains from current insurance coverage.